Analysis of the Application of Accounting Information Systems In Micro, Small and Medium Enterprises (MSMEs) - Juni Cahyani; Luke Suciyati Amna (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2022)
Abstract Micro, Small and Medium Enterprises (MSMEs) are a fundamental business pillar for the Indonesian economy. In MSMEs, capital is not the only problem that must be faced, but it must also be seen from the side of capital management to be considered so that business activities can run well and maximally. The problem found by researchers related to the Accounting Information System (AIS) in MSMEs is the decline in income in 2020 and 2021. One of the causes is the absence of correct accounting records. This study aims to determine the implementation of AIS in MSMEs and study the inhibiting aspects. The case study was conducted using descriptive qualitative research conducted at the Asira Food Store located in Wonomarto Village, North Kotabumi, North Lampung, Lampung. The result of this research is that Asira Food UMKM has not implemented an Accounting Information System.